2011
DOI: 10.1371/journal.pone.0016362
|View full text |Cite
|
Sign up to set email alerts
|

Flux Balance Analysis of Ammonia Assimilation Network in E. coli Predicts Preferred Regulation Point

Abstract: Nitrogen assimilation is a critical biological process for the synthesis of biomolecules in Escherichia coli. The central ammonium assimilation network in E. coli converts carbon skeleton α-ketoglutarate and ammonium into glutamate and glutamine, which further serve as nitrogen donors for nitrogen metabolism in the cell. This reaction network involves three enzymes: glutamate dehydrogenase (GDH), glutamine synthetase (GS) and glutamate synthase (GOGAT). In minimal media, E. coli tries to maintain an optimal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…GS regulation provided a greater robustness of the fluxes against perturbations of enzyme or ammonium concentrations, in particular when the ammonium supply fluctuated (569). A flux balance model for nitrogen metabolism was developed (570) and verified by experiments carried out for the wild-type and GDH and GOGAT knockout strains (135,567). Furthermore, by employing the kinetic equations built for GS, GDH, and GOGAT (44), Yuan et al were able to predict maximal capacities of the three enzymes in wild-type and mutant strains as a function of the ammonium availability.…”
Section: Estimating Fluxes In Vivomentioning
confidence: 99%
“…GS regulation provided a greater robustness of the fluxes against perturbations of enzyme or ammonium concentrations, in particular when the ammonium supply fluctuated (569). A flux balance model for nitrogen metabolism was developed (570) and verified by experiments carried out for the wild-type and GDH and GOGAT knockout strains (135,567). Furthermore, by employing the kinetic equations built for GS, GDH, and GOGAT (44), Yuan et al were able to predict maximal capacities of the three enzymes in wild-type and mutant strains as a function of the ammonium availability.…”
Section: Estimating Fluxes In Vivomentioning
confidence: 99%
“…Among various nitrogen sources, bacteria prefer ammonia, which supports a fast growth rate in E. coli compared with alternative nitrogen sources such as amino acids ( 13 ). It has been confirmed that the Ntr system maintains a fast growth rate across a wide range of ammonium concentrations, primarily by regulating both the expression and activity of the glutamine synthesis enzyme GS (glutamine synthetase) and also of the ammonium transporter AmtB ( 5 , 14 16 ).…”
Section: Introductionmentioning
confidence: 97%
“…During a cultivation, the pH is drifting as result of conversion and production of substrates and metabolic compounds. One such substrate is ammonium, which is a preferred nitrogen source supporting fast growth rates [ 6 , 7 ]. Although the direct uptake of ammonium is possible through the transporter protein AmtB at very low ammonium levels or low pH environment [ 8 ], the usual uptake is through free diffusion of uncharged ammonia through the cell membrane [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%